Smart Library Access And Management System (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In the present day scenario in colleges and schools we use a costly interface just to access library and process the attendance system. But to satisfy these requirements we don’t require such costly interfaces. Generally RFID tags are used as the interface between the stored database and the students. But we have brought a cost efficient system excluding the RFID usage and providing a photographic interface to the students. The main idea of this project is to apply the software knowledge of LabVIEW and image processing. LabVIEW plays the major role in acquiring real time data and processing it as an image. As an Instrumentation Engineer, we use LabVIEW as the tool for building, testing and deployment of Virtual Instruments that can be further developed into fully functional blocks. These Functional blocks comprise of NI-VISION and MOTION modules that aid in the precise processing of image data and image acquisition. A USB2.0 PC camera is used to capture the image of the identity card and the access code printed on the book. The captured image from the camera is subjected to a series of computation in Vision Assistant module and the machine training details are saved. The processed data is linked with the database using suitable connectivity techniques. To make it more innovative, database connectivity is ensured using MS SQL, an online server which holds the data of the books and the details of the students. This online server provides an additional advantage of accessing the database throughout the connected devices. Also a dual interface approach is carried out which provides the librarian end and thee student end of access to the system. This makes the processing and the usage very easy and simple to the student.